Standards-Based Physical Education in Schools: The Role of State Laws. Issue 2 (2021) - Sprow, Kyle; Perna, Frank M.; Leider, Julien; Turner, Lindsey; Piekarz-Porter, Elizabeth M.; Michael, Shannon L.; Brener, Nancy; Chriqui, Jamie F.
Abstract : ABSTRACT: This study aimed to examine the association of state physical education (PE) laws (https://class.cancer.gov ) with school policies addressing motor skill development, physical activity participation, and health-enhancing physical fitness (https://www.cdc.gov/healthyyouth/data/shpps/data.htm ). National school-level data on PE standards were obtained from the 2014 School Health Policies and Practices Study of U.S. schools for analytical samples of 408–410 schools in 43 states. These data were linked to the Classification of Laws Associated with School Students data, which reflect the strength of state PE curriculum laws and the associated state PE curriculum standards. Logistic regressions and generalized linear models with a complementary log–log link examined associations between state law and school-level standards. Compared with having no state law, weak law (odds ratio [OR] = 5.07, 95% confidence interval [CI] = 1.02–25.27) or strong law (OR = 2.96, 95% CI = 1.04–8.37) was associated with higher odds of school PE standards addressing motor skill development, whereas only strong state law was associated with higher prevalence of addressing achievement and maintenance of physical fitness (coefficient = 0.63, 95% CI = 0.12, 1.14). State laws were not associated with addressing physical activity participation. Schools were more likely to address motor skills and physical fitness development when states had strong PE laws.